UPAYA MENINGKATKAN KINERJA GURU DALAM KOMPETENSI MENGAJAR DIKELAS MELALUI PENERAPAN REWARD AND PUNISHMENT DI UPT.SD. NEGERI 12 DAHARI INDAH KABUPATEN BATU BARA - Wahab, Abdul (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2022)
In an effort to produce quality education in schools, many factors or components are involved, both human and non-human. School is a complex and unique organization, so its implementation requires high coordination with all its components. The principal as a direct leader is a real example in the work activities of his subordinates. A school principal who is diligent, careful, cares about his subordinates, will be different from leadership that is indifferent, less communicative, let alone arrogant with the school community. School culture is a positive thing that must be maintained and implemented by all school members without feeling forced. One of the school cultures that must be maintained is the issue of performance, including the performance of teachers in classroom competence in the teaching and learning process. To improve the performance of teachers, efforts can be made through various methods. In this School Action Research (PTS), action was attempted in the form of implementing Reward and Punishment for teachers at SD Negeri 12 Dahari Indah, Tala Wi District, Batu Bara Regency. This research was carried out in two cycles, because of the results of research and data analysis. It turns out that in the second cycle, teacher performance in classroom competence in the teaching and learning process increased and met the predetermined indicators of 75%. From the results of this research, it can be concluded that improving teacher performance in classroom competence in teaching and learning activities can be done by implementing Reward and Punishment for teachers.